2010
DOI: 10.1103/physrevd.82.074006
|View full text |Cite
|
Sign up to set email alerts
|

Complete(O7,O8)contribution toB¯X

Abstract: We calculate the set of Oð 2 s Þ corrections to the branching ratio and to the photon energy spectrum of the decay process "B ! X s originating from the interference of diagrams involving the electromagnetic dipole operator O 7 with diagrams involving the chromomagnetic dipole operator O 8 . The corrections evaluated here are one of the elements needed to complete the calculations of the " B ! X s branching ratio at next-to-next-to-leading order in QCD. We conclude that this set of corrections does not change … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…the calculation in ref. [27] revealed that the α 2 s β 0 term is not a good approximation to the full result. In light of this finding we do not advocate the use of naive non-abelianization in our case.…”
Section: Jhep10(2017)191mentioning
confidence: 97%
“…the calculation in ref. [27] revealed that the α 2 s β 0 term is not a good approximation to the full result. In light of this finding we do not advocate the use of naive non-abelianization in our case.…”
Section: Jhep10(2017)191mentioning
confidence: 97%
“…(3)(4), as the remaining ones can be neglected due to their small Wilson coefficients. The Q 7 -Q 7 and Q 7 -Q 8 interference terms are already known at O(α 2 s ) in a complete manner [32][33][34][35][36]. The NNLO interference terms not involving Q 7 can be separated into two-body final state contributions (trivially derived from the NLO results) or relatively small (n ≥ 3)-body final state contributions that have been calculated so far [37][38][39] only in the Brodsky-LepageMackenzie (BLM) [40] approximation.…”
Section: The Ratio R γ In the Sm And 2hdmmentioning
confidence: 99%
“…The allowed region depends on higherorder QCD effects. A huge effort has been made devoted to the calculation of these corrections, the bulk of which are the same as in the SM [164][165][166][167][168][169][170][171][172][173][174][175][176][177][178][179][180][181][182][183]. They are now complete up to NNLO order.…”
Section: Constraints From H + Loop-level Exchangementioning
confidence: 99%